The UN Sustainable Development Goals as innovation drivers for local sustainability governance? Examples from Germany. - (:unkn) unknown (My University, 2022)
Local governments are highly relevant for the just-starting socio-ecological transformation. Living up to this role requires new or adapted forms of governance. The German case provides a vivid example of how the UN Sustainable Development Goals (SDGs) provide a useful framework for this transformation. In our policy-oriented contribution, we focus on the question whether the SDGs themselves are innovation drivers in local sustainability governance. We motivate this idea with the theoretical framework of public sector innovation and provide comprehensive examples of the most prevalent current approaches to SDG-related innovations at the German local government level, covering local government sustainability reporting, strategies, budgets, and financing. Our central finding is that a small group of early-innovating German local governments has already begun to govern sustainability with the help of SDG-driven innovations and that this became possible because of publicly funded support projects and accessible pre-defined localised SDGs.
Keywords: Sustainable Development Goals (SDG); Nachhaltigkeitsziel; Öffentlicher Sektor; Nachhaltige Entwicklung; Nachhaltige Stadtentwicklung; Kommunale Selbstverwaltung; Governance; Innovation